Different approaches to relating genotype to phenotype in developmental disorders. - Karmiloff-Smith, A; Scerif, G; Thomas, M (2002)
In this article, we discuss the complex problem of relating genotype to phenotype and challenge the simple mapping of genes to higher level cognitive modules. We examine various methods that have been used to investigate this relation including quantitative genetics, molecular genetics, animal models, and in-depth psychological and computational studies of developmental disorders. Both single gene and multiple gene disorders indicate that the relationship between genotype and phenotype is very indirect and that, rather than identifying mere snapshots of developmental outcomes, the process of ontogenetic development itself must be taken into account.